Fall risk assessment in elderly with and without history of falls: strength analysis of lower limb: a comparative study - Coutinho, António (2014)
Objectives: The objective of this research was to analyse muscle performance criteria of the knee joints and ankle flexor and extensor muscles among elderly with and without history of falls. Material and methods: The sample was non-probabilistic, of convenience, comprising a total of 30 elderly (15 with history of falls and 15 without history of falls) who met the inclusion and exclusion criteria. Data were collected through a characterization questionnaire and through the Biodex System Isokinetic Dynamometer. The isokinetic assessment consisted in collecting the Peak Torque per unit of mass (N.m/BW) and ratio FlexorsCon/ExtensorsCon (%) of the knee joints and ankle flexor and extensor muscles, with 5 repetitions and the 60º/s angular speed. This collection has been made in both lower limbs. Results: The sample consisted of 30 individuals, 15 from the group without history of falls and 15 from the group with history of falls with average age of (69,17±4,77) years old. The muscle performance parameters were not significantly different between the groups (p>0,05). Conclusion: The group of elderly with history of falls showed lower Peak Torque numbers per unit of mass (N.m/BW) for the knee and ankle joint comparing with the group without history of falls. In present research also the values of the ratio flexorsCon/ExtensorsCon was analyzed weren't differences found in the knee and ankle joint. Although there are no statistically significant differences between results obtained, approach we believe it will be beneficial to include strengthening exercises for the flexors and extensors muscles of these joints, thereby contributing to the prevention of falls.